Exploring the potential of house crickets (Acheta domesticus) in future agri-food systems - Psarianos, Michail Marios; Justus Liebig University Giessen (My University, 2023)
Edible insects, particularly house crickets, are gaining recognition as a vital resource in the food industry due to their minimal environmental footprint, high nutritional value, and contribution to a circular economy. This makes them a promising candidate for addressing the need for sustainable and resilient agri-food systems. Various innovative approaches in food production can enhance their efficiency and impact on product quality. The thesis focuses on implementing innovative methods in the production chain of house crickets to evaluate their effectiveness and influence on product quality. Firstly, indoor farming systems capable of hosting multiple organisms were explored, with artificial illumination identified as crucial. LED lights combined with narrowband UV-B radiation were applied to the rearing process, resulting in improved growth and survival rates of house crickets. The addition of UV-B radiation enhanced protein and chitin content, making the artificial light system suitable for their development and potential co-rearing with other organisms. In the post-harvest stage, non-thermal processing methods were employed to produce cricket-based flour. Pulsed electric fields (PEF) processing accelerated drying rates, reducing energy consumption while enhancing flour quality. Electrohydrodynamic drying (EHDD) was also assessed for its energy efficiency, although it proved less effective alone. However, combining PEF with conventional drying significantly reduced processing time and energy consumption by over 50%. PEF processing not only improved the efficiency of conventional processing but also facilitated the extraction of intracellular compounds from crickets, including fats and proteins. Further exploration of emerging food processes such as ultrasound (US) and high pressure (HP) treatments, along with the use of deep eutectic solvents (DES), allowed for the valorization of cricket flour into valuable ingredients. These processes led to the successful recovery of fats, phenolics, proteins, and chitin, with US increasing phenolic compound extraction yield and DES separating proteins from chitin effectively. Chitin extraction, crucial for producing chitosan with various applications, traditionally involved hazardous materials. Alternative methods including DES, enzymatic treatment, fermentation, and microwave treatment were explored. A novel processing pathway involving fermentation with Lactococcus lactis and enzymatic digestion with bromelain resulted in a chitin-rich fraction with high chitosan yield (> 85%), exhibiting antioxidant and antimicrobial properties, along with efficient wastewater purification capabilities. Overall, this thesis demonstrates the effectiveness of innovative food production methods in enhancing the quality of cricket-based products while minimizing environmental impact. Integrating these methods into future agri-food systems could contribute significantly to sustainability and resilience.
Keywords: edible insects; agri-food systems; emerging technologies; food processing; ddc:630